Optical Properties of ZnO-Alloyed Nanocrystalline Films. (14th May 2012) - Che, Hui; Huso, Jesse; Morrison, John L.; Thapa, Dinesh; Huso, Michelle; Yeh, Wei Jiang; Tarun, M. C.; McCluskey, M. D.; Bergman, Leah
Abstract : ZnO is emerging as one of the materials of choice for UV applications. It has a deep excitonic energy level and a direct bandgap of ~3.4 eV. Alloying ZnO with certain atomic constituents adds new optical and electronic functionalities to ZnO. This paper presents research on M g x Z n 1 − x O and Z n S 1 − x O x nanocrystalline flexible films, which enable tunable optical properties in the deep-UV and in the visible range. The ZnO and Mg 0 .3 Zn 0 .7 O films were found to have bandgaps at 3.35 and 4.02 eV, respectively. The photoluminescence of the Mg 0 .3 Zn 0 .7 O exhibited a bandedge emission at 3.95 eV, and at lower energy 3.38 eV due to the limited solubility inherent to these alloys. ZnS 0 .76 O 0 .24 and ZnS 0 .16 O 0 .84 were found to have bandgaps at 3.21 and 2.65 eV, respectively. The effect of nitrogen doping on ZnS 0 .16 O 0 .84 is discussed in terms of the highly lattice mismatched nature of these alloys and the resulting valence-band modification.